2016
DOI: 10.1161/circimaging.116.005343
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Coronary Plaque Microstructure Differences Between Women and Men

Abstract: The difference between men and women is getting harder and harder to invent.-Marty Rubin C ardiovascular disease remains the leading cause of death in men and women in the United States. Over the past 2 decades, both clinicians and researchers have paid increased attention to the problem of cardiovascular disease in women, with some improvements in the recognition of the problem and in outcomes. Historically, women with acute coronary syndrome (ACS) have had worse outcomes. However, with the improvement in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Interestingly, sex differences in the atherosclerotic phenotype observed in Apoe −/− mice have been well-defined, whereby females tend to have larger plaques and increased calcification in those plaques [ 136 ]. Conversely, in human patients, females typically have smaller plaques and less calcification within the plaques [ 137 ]. Whilst investigations are frequently limited by the focus on a single sex, those rodent studies that have employed males and females to interrogate cardiovascular calcification pathways ( Table 1 ), have produced divergent findings; highlighting the constraints of these animal models, and the importance of investigating both sexes in pre-clinical studies.…”
Section: Animal Models Offer Insights Into Sex Differences In Cardiovascular Calcificationmentioning
confidence: 99%
“…Interestingly, sex differences in the atherosclerotic phenotype observed in Apoe −/− mice have been well-defined, whereby females tend to have larger plaques and increased calcification in those plaques [ 136 ]. Conversely, in human patients, females typically have smaller plaques and less calcification within the plaques [ 137 ]. Whilst investigations are frequently limited by the focus on a single sex, those rodent studies that have employed males and females to interrogate cardiovascular calcification pathways ( Table 1 ), have produced divergent findings; highlighting the constraints of these animal models, and the importance of investigating both sexes in pre-clinical studies.…”
Section: Animal Models Offer Insights Into Sex Differences In Cardiovascular Calcificationmentioning
confidence: 99%
“…19 Thus, females may develop symptoms even with smaller plaque burden or thrombus load. 20,21 It has been reported that increasing cardiac fat deposition, measured by volumetric analysis rather than linear thickness assessment, is significantly associated with the presence of high-risk plaque features in a systematic review and meta-analysis of 9 studies. This association may be mediated via cellular cross-talk which may lead to the development of plaque characteristics considered to be "high risk" given their association with major adverse coronary events.…”
Section: Discussionmentioning
confidence: 99%